(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Abstract - Heart diseases greatly affect the individual and the health care budget of a developing country like India. Objectives – 1. To evaluate the effectiveness of structured teaching programme regarding emergency management of myocardial infarction for staff nurses.2.To find out the association between pre-test knowledge of staff nurses their selected demographic variables. Methodology- Evaluative approach with quasi experimental research design was used. Data was collected from 200 staff nurses with the help of structured knowledge questionnaire. Data was analysed with inferential and descriptive statistics. Results- The overall mean of pre test score is 20.81 whereas the mean of post test score is 26.06 with 5.25 mean differences. The median of pre test score is 21 and the mean of post test score is 26 and the standard deviation of pre test was 2.25 whereas in post test the standard deviation was 2.95. The t value is 20.46. Summery- structure teaching programme was effective regarding emergency management of myocardial infarction patients among staff nurses